THE METHOD OF BUILDING THE OPTIMAL EDUCATIONAL TRAJECTORY OF HIGHER EDUCATION ACQUISITIONERS - MALAIKO, Andrii; PASICHNYK, Olexander; SKRYPNYK, Tetana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
With today’s lectures and lessons, rules and bells, we continue to use an industrial model of education designed to produce factory workers. Students learn to agree with the masses, but they do not learn to think for themselves. Subjects are taught in isolation, as a result of which students do not understand how all knowledge is interconnected. Our current system undermines the ability of parents to guide the moral formation of their children. Fathers and mothers are denied a voice in the values taught in our schools. Many school districts believe that once a student enters the school’s doors, parents no longer have jurisdiction. A careful examination of modern education reveals that it is not education at all. Our current system has at least three fundamental flaws: a misplaced focus on right knowing instead of right being, a lack of instruction on how to recognize truth and communicate it profitably, and a disintegration of subjects without teaching how things fit together. One of the solutions to a number of modern educational problems can be to study according to the optimal educational trajectory, which forms a large baggage of knowledge for the student for his future professional activity. This also means that a highly qualified specialist will easily enter the labor market. It is possible to enumerate the strengths of quality education for quite a long period of time, but the question arises: how exactly to form this education? How to make the learning process as interesting and productive as possible for the student? At the moment, there are quite a lot of training programs, and it is hardly possible to create something completely new. But no one canceled the option with the modification of the existing program. Therefore, this scientific work proposes a method of building an educational trajectory, which uses to build a list of mandatory and optional disciplines that cover a set of necessary competencies.